The state of physical training of servicemen of Internal Affairs of Ukraine on the stage of professional becoming - Вереньга Юрій Володимирович, (Yuriy Verenga) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: to explore the level of development of physical qualities of servicemen of Internal Affairs of Ukraine with different duty-post categories on the stage of the professional becoming. Material and Methods: the study involved 104 servicemen of the first age group with different duty-post categories: 1-st – 32, 2-d – 37, 3-d – 35. The results from a run on 100 m, pulling up on a cross-beam and a run on 1000 m during preliminary examinations on the courses of primary training were analyzed. Results: it is set, that the level of physical preparedness of servicemen on the stage of the professional becoming is insufficient. The lowest level of physical preparedness is definite at the servicemen of 1-st category (r<0,05–0,001). Among physical qualities the worst level of the servicemen of all categories is fixed in the indexes of endurance. Conclusions: the results of research testify to necessity of improvement of the operating program from physical training with the servicemen of 1-st category on the courses of primary training by the increasing of level of basic physical qualities (endurance in particular).